1981
DOI: 10.1093/ajcn/34.4.807
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional supplementation, maternal education, and cognitive development of infants at risk of malnutrition

Abstract: Infants born to families at risk of malnutrition were studied prospectively from the beginning of the 3rd trimester of the mother's pregnancy until the child reached 3 yr of age to ascertain the effects of nutritional supplementation and/or a maternal education program on their cognitive development. Four hundred thirty-three families were assigned randomly to six groups: group A served as a control; group B received the supplement from the age of 6 months to 3 yr; group C received the supplement during the 3r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
7

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 4 publications
4
124
0
7
Order By: Relevance
“…85,86 A few trials of energy supplementation have also indicated improved cognitive development for undernourished children or those at high risk of malnutrition. [87][88][89] Our finding that linear growth in the first 2 years of life appears to be a stronger independent predictor of both early and later childhood cognition as compared with growth after 2 years of age also corroborates a growing body of neuroscientific research showing that exposure to environmental and biological adversity during early sensitive periods of brain development can be particularly detrimental to cognitive development. 90 We found a significantly muted cross-sectional association of HAZ with cognition for children .2 years old.…”
Section: Figuresupporting
confidence: 80%
“…85,86 A few trials of energy supplementation have also indicated improved cognitive development for undernourished children or those at high risk of malnutrition. [87][88][89] Our finding that linear growth in the first 2 years of life appears to be a stronger independent predictor of both early and later childhood cognition as compared with growth after 2 years of age also corroborates a growing body of neuroscientific research showing that exposure to environmental and biological adversity during early sensitive periods of brain development can be particularly detrimental to cognitive development. 90 We found a significantly muted cross-sectional association of HAZ with cognition for children .2 years old.…”
Section: Figuresupporting
confidence: 80%
“…One study reported that food supplementation for pregnant mothers in their third trimester and for infants up to six months of age did not benefit growth of children with LBW (Waber, et al, 1981). This supports that foetal and infant growth and development is dependent on maternal nutrition (Wu, et al, 2004), whereby growth is most susceptible to deficiencies of nutrients (protein and micronutrients) during implantation (day five to ten postfertilisation) and the period of rapid placental development (first trimester of gestation) (Waterland and Jirtle, 2004).…”
Section: Intrauterine Growth Restrictionmentioning
confidence: 98%
“…The answer may be found in hypotheses which speculate that energy supplementation itself may have differential effects for boys and girls, because of systematic sex differences in temperament (Barrett & Frank, 1987;Waber et al, 1981). Increases in energy for boys may lead to increased toddler`masculine behaviors', ie more high-energy, gross-motor type activities, such as climbing on furniture or running around the room or outside.…”
Section: Genderâtreatment Effectsmentioning
confidence: 99%